Pharmacist as Pharmacovigilance Practitioner - Janarthanan, Vijay Venkatraman; Ramakrishnan, Ganesan; Krishnamurthy, Subashchander; Sahar, Akash Imayam (Indian Journal of Pharmacy Practice)
Pharmacy as a profession has made significant progress in the recent years. It has seen a paradigm shift from product orientation to patient focus. Pharmacist should realize it’s no more a task carried out behind the curtains. This article introduces aspiring pharmacists to one such profession where they can extend their roles as providers of service which promotes drug safety.
Keywords: ADR; Drug safety; Pharmacovigilance; Pharmacist; PVPI